An evaluation of the UPCD clinicians' readiness for the theoretical part of the Philippine dental board examination prior to graduation and review - Goquiolay, Ma. Prescilla F.
The Philippine Dental Board Examination will soon be realized by the senior students of the University of the Philippines College of Dentistry. Acquisition of skills and knowledge in Dentistry begins during the first year of education in this institution. At this stage in the clinicians' training, will they have acquired sufficient knowledge to qualify for the theoretical part of the Philippine Dental Board Examination? This paper attempted to find that out on the basis of the administered "Mock Board Examination" which was derived by the researches from the December 1986 licensure examination. Results reveal that a proportion of 0% students passed the examination as against 100% students failed which led to the conclusion that the UPCD clinicians, are not ready to take the Philippine Dental Board Examination, theoretical part.